Formulation and Evaluation of Licorice-Extract-Enhanced Chitosan, PVA, and Gelatin-Derived Hydrogels for Wound Dressing - Maria Mujahid; Muhammad Zubair; Asma Yaqoob; Sohail Shahzad; Aman Ullah (Bioengineering)
Wound infections remain a significant clinical challenge, impeding healing and causing deterioration. Recently, multifunctional hydrogel dressings have gained interest as an effective treatment to treat infections efficiently and enhance wound recovery. The present research is focused on the development of composite hydrogels comprising chitosan (CS), polyvinyl alcohol (PVA), gelatin (GEL) and licorice extract (LE), using the freeze gelation technique. The resulting composite hydrogels of CS/PVA/GEL incorporating LE were characterized by FTIR, XRD and SEM. FTIR analysis confirmed the presence of specific functional groups within the molecules. XRD exhibited the amorphous nature of hydrogels. SEM analysis revealed that increasing the CS ratio in hydrogels created a more porous structure with a smaller pore size. All the hydrogels demonstrated oxygen permeability, which is crucial for the healing process. Among the synthesized hydrogels, MM-2 containing PVA (20 mL) and LE (4 mL) demonstrated superior performance with a water retention capacity of 440% and moisture content of 91%. This exceptional result can be attributed to the higher proportion of PVA and the material’s porous structure, which enhances its hydrophilic properties. The synthesized hydrogels showed good antibacterial potential against three selected strains of bacteria including Bacillus subtilis (B. subtilis), Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The hydrogels’ cytotoxicity levels were assessed through hemolysis assay and the results demonstrated that all hydrogels were non-toxic. The hydrolytic breakdown revealed that the interconnected hydrogels with licorice components exhibited slow degradation, making them more appropriate for long-term wound treatment. Specifically, MM-4 demonstrated a 74% degradation rate and displayed 75% antioxidant activity, indicating its potential effectiveness for chronic wound applications. These characteristics of synthesized CS/PVA/GEL/LE-derived hydrogels suggest their potential use as a promising candidate for wound care applications.